A criação de amigos imaginários: um estudo com crianças brasileiras - Velludo, Natália Benincasa (Universidade Federal de São Carlos, 2014)
The creation of imaginary companions is a phenomenon that has been timidly explored in the international literature in Psychology and Psychiatry. More specifically, there are still important questions regarding who are the children that create imaginary companions and the role that fantasy plays in emotional and cognitive development. In recent years, several studies investigating symbolic play have been conducted in Brazil, however, according to three different data bases (SciELO-Brasil, Index Psi, PePSIC), there are only two national studies on the topic of imaginary companions, suggesting a yet limited understanding of the manifestation of this phenomenon in Brazilian children. Considering this gap in the literature, as well as the potential contributions of studies on this type of fantasy, the present research aimed, therefore, to investigate this form of pretend play in a sample of Brazilian children, and to be the first study in Brazil to investigate the relationship between the creation of imaginary companions and sociocognitive development. Our hypothesis was that children with imaginary companions would have significantly higher scores than the comparison group in measures of language, social cognition and engagement in fantasy. Forty children between 6 and 7 years of age (M age = 7;1, SD = 5.29), 21 girls and 19 boys, participated in the study and were recruited from an elementary public school in a city located in the state of São Paulo. Eighteen participants were included in the group of children who reported an imaginary companion and 22 in the group of children who did not. To test for possible differences between the two groups, three measures of theory-of-mind, emotional comprehension and language were used, as well as an interview about fantasy orientation and the characteristics of their imaginary companions. In addition, a questionnaire assessing socioeconomic status and an interview about the family and the child s fantasy world were administered to 11 participating caretakers. As predicted, children s reports of imaginary companions were rich and seemed to serve similar functions to the ones found in previous international studies (e.g., company, fun, emotional support). Children with imaginary companions had higher vocabulary scores than children who did not report them, but no significant differences were found between the two groups with regard to theory of mind and emotional comprehension. Such line of research can help to demystify this form of pretend play, to which little attention is given in the media and in the scientific community, as well as to collaborate with the instruction of parents and educators on the creation of imaginary companions, and finally, to contribute to international research by providing data from a specific culture. Moreover, the present study provides evidence that the creation of imaginary companions is not associated with any developmental deficits; on the contrary, it can be a predictor of more sophisticated abilities such as higher vocabulary.
The creation of imaginary friends: a study with brazilian children
Keywords: Psicologia; Desenvolvimento cognitivo; Brincadeira simbólica; Desenvolvimento infantil; Amigos imaginários; Faz de conta; Imaginary companions; Pretend play; Schoolchildren; Social cognitive development; CIENCIAS HUMANAS::PSICOLOGIA